2020
DOI: 10.1111/jam.14563
|View full text |Cite
|
Sign up to set email alerts
|

A compound isolated from Alpinia officinarum Hance. inhibits swarming motility of Pseudomonas aeruginosa and down regulates virulence genes

Abstract: Aim:The study was aimed at purifying the active principle from Alpinia officinarum rhizomes responsible for inhibition of swarming motility of Pseudomonas aeruginosa and analysing the mechanism of action. Methods and Results: The active compound from methanol extract of A. officinarum was purified by silica gel column chromatography followed by elution from Amberlite resin. The compound 1-(3,5-dihydroxyphenyl)-2-(methylamino)ethan-1-one, inhibited swarming motility at 12Á5 µg ml À1 . This inhibition was indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Previous studies have also reported antibacterial activity of the rhizomes of A. officinarum Hance [5,[8][9][10][11]. For example, Lee and Rhee reported that the methanol and ethylacetate combination extracts from fresh rhizomes of A. officinarum Hance were especially effective against four vancomycin-resistant Enterococci strains: E. faecalis (K-10-22), E. faecaium (K-11-212), E. faecalis (K-10-57) and E. faecalis (K-10-361), with MIC values of 12.5, 12.5, 6.25 and 25 µg/mL, respectively.…”
Section: Antibacterial Activity Of Chloroform-and Methanol-phase Extr...mentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies have also reported antibacterial activity of the rhizomes of A. officinarum Hance [5,[8][9][10][11]. For example, Lee and Rhee reported that the methanol and ethylacetate combination extracts from fresh rhizomes of A. officinarum Hance were especially effective against four vancomycin-resistant Enterococci strains: E. faecalis (K-10-22), E. faecaium (K-11-212), E. faecalis (K-10-57) and E. faecalis (K-10-361), with MIC values of 12.5, 12.5, 6.25 and 25 µg/mL, respectively.…”
Section: Antibacterial Activity Of Chloroform-and Methanol-phase Extr...mentioning
confidence: 90%
“…This inhibition was independent of rhamnolipid production. Real-time PCR analysis showed significant downregulation of virulence-associated genes, including T3SS exoS, exoT and the flagella master regulator fleQ [10].…”
Section: Introductionmentioning
confidence: 99%
“…In P. aeruginosa, twitching is modulated by type IV pili and is evident on solid surfaces [79], while swarming is a coordinated group movement on semi-solid surfaces that requires both flagella and type IV pili, and as such, it is regulated by QS [80]. Swimming, on the other hand, occurs in a liquid environment and also requires the use of flagella [79,81]. All those motilities play a determining role in bacterial attachment, colonization and their ability to cause widespread infections [7].…”
Section: Discussionmentioning
confidence: 99%
“…The invasive nature and success of P. aeruginosa in colonising diverse environments is accounted for by twitching/ swarming motilities [105,106], that are modulated by QS pathways with the aid of flagellar movement, to sense and move towards favourable environments [107,108]. A number of regulatory genes are required in flagellar biosynthesis including the anti-sigma-28 factor protein (encoded by flgM) that regulates expression of the B-type flagellin (encoded by fliC) [109], and flgG-encoded flagellar basal-body rod protein FlgG which mediates flagellar rod assembly [110,111].…”
Section: Discussionmentioning
confidence: 99%